Novel Gas Barrier SiOC Coating to PET Bottles through a Hot Wire CVD Method. (27th June 2016) - Nakaya, Masaki; Kodama, Kenji; Yasuhara, Shigeo; Hotta, Atsushi
Abstract : In an attempt to enhance the gas barrier enhancement of plastic containers such as poly(ethylene terephthalate) bottles, a novel method was found using a hot wire CVD technique, where tantalum wire is heated and exposed to a gas flow of vinyl silane. The resultant SiOC thin film was confirmed to characteristically contain Si-Si bonds in its surface and demonstrate a remarkably and highly practical decrease of the permeation of various gas through poly(ethylene terephthalate) bottles.